PENGARUH KETERAMPILAN KEWIRAUSAHAAN, MODAL USAHA, DAN AKSES PASAR TERHADAP PENDAPATAN DIVERSIFIKASI OLAHAN IKAN DI DESA BATUTUA - Melkianus Teddison Bulan; Alfrido Naiheli (ZIRAA'AH MAJALAH ILMIAH PERTANIAN, 2026)
Efforts to diversify local processed fish products in Batutua Village, Rote Ndao Regency, have the potential to increase coastal community income but still face challenges related to processing skills, limited capital, and market access. This study aimed to analyze the influence of entrepreneurial skills, business capital, and market access on business income, both simultaneously and partially, and to determine the dominant influencing variable. The population consisted of 30 business actors, all selected as samples using a saturated sampling technique. The results showed that simultaneously, all three variables significantly influenced business income, with an Adjusted R-Square value of 0.738. Partially, only entrepreneurial skills had a significant effect and emerged as the dominant variable, with a Beta value of 0.737. This study concludes that enhancing business actors' skill capacity is a key factor in increasing income from processed fish diversification businesses.